A case of multiple genomic anomalies (the combination of Ehlers — Danlos syndrome vascular type and Loeys — Dietz syndrome type 2) in a child - A. E. Sipyagina; L. S. Baleva; E. N. Yakusheva; A. N. Semyachkina; E. A. Potrokhova (Лечащий Врач)
Hereditary connective tissue diseases are widespread in the world. There are doctors of various specialities: pediatricians, surgeons, as well as doctors of narrow specialties: cardiologists, ophthalmologists and others, which deal with syndromes, included in this group of diseases. Currently, verification of the nosological form of hereditary connective tissue diseases remains difficult, due to a large variety of mutations, as well as pronounced clinical polymorphism of phenotypic manifestations of diseases. The report presents a clinical case of a patient with polygenic connective tissue disorder: a combination of autosomal dominant Ehlers – Danlos and Loeys – Dietz syndromes. In the modern literature, we have not found a description of the combination of these two syndromes in one individual. When assessing clinical symptoms, it was found that there was no necessary and sufficient complex of phenotypic manifestations of Ehlers – Danlos syndrome, vascular type. In the presence of ophthalmological symptoms (increasing ophthalmia – buftalm), vascular changes and funnelshaped deformity of the chest, there were no data for pronounced hypermobility of the joints, high skin extensibility, changes in the internal hollow organs. This dictated the need for further verification of the diagnosis – a full-exome scan was performed with the detection of a mutation in the heterozygous state in the TGFBR2 gene of chromosome 3 (exon 5), which leads to the appearance of Loeys – Dietz syndrome type 2 with pronounced tortuosity of arterial vessels, including cerebral, the presence of aneurysmal outgrowth, with the formation of kyphosis, with gradual expansion and weakening of the dura mater. However, the child did not have such frequently observed symptoms as congenital heart defects and aortic aneurysms, facial anomalies. The presence of two syndromes with an autosomal dominant type of inheritance in one patient at the same time can probably have an additive effect and change phenotypic signs. The article shows the need for medical and genetic counseling of the family and long-term multidisciplinary supervision of the child.